Evaluation of the implementation of the circular economy in EU countries in the context of sustainable development - Myroslav Kryshtanovych; Viktoriia Filippova; Maryna Huba; Olga Kartashova; Oleksandr Molnar (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The circular economy is interpreted as a stable economic system, which aims at eliminating the consequences and costs, as well as providing a constant cycle of necessary resources. That is why it is so important to conduct its assessment today. The object of the article is the state of the circulating economy of the leading countries of the world. The purpose of the article is to assess the possibilities and mechanisms of the circular economy in the context of the introduction of the European Union. The methodological basis is a system of mutually complementary general scientific and special methods of cognition. To assess the quality of the implementation of the circular economy, we have chosen the recycling method as the most relevant and easiest to use. The study examined the essence, progress, principles and main advantages of using the circular economy model in the context of implementing this model in 20 countries of the European Union, and the model for analysing the processing possibilities in the European Union as a basic tool for assessing the implementation of a circular economy are presented.
Keywords: A14; O11; O13; Q01; Q50; 650; circular economy; linear economy; stability; recirculation; manufacturing process; waste; process material